2023
DOI: 10.3390/ijerph20020988
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness as a Predictor of Performance during Competition in Professional Women’s Basketball Players

Abstract: The evaluation of physical fitness in team sports is enjoying greater importance in the training of professional teams. The objectives of this research were to characterize physical fitness and game indicators based on the game position. This is an empirical study, with a quantitative, descriptive and cross-sectional methodology. In addition, different relationships between the level of physical fitness and the game indicators during the competition were determined. Finally, a predictive analysis of the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
2
16
0
3
Order By: Relevance
“…While an altitude effect occurred across all playing positions, the workload magnitudes differed between guards, forwards, and centers. Playing positions present different roles during the game that affect physical [19,20] and technical-tactical actions [21]. Guards covered more distance in high-speed running, change in direction, and acceleration/deceleration versus forwards and centers.…”
Section: Specific Demands Between Playing Positionsmentioning
confidence: 99%
See 2 more Smart Citations
“…While an altitude effect occurred across all playing positions, the workload magnitudes differed between guards, forwards, and centers. Playing positions present different roles during the game that affect physical [19,20] and technical-tactical actions [21]. Guards covered more distance in high-speed running, change in direction, and acceleration/deceleration versus forwards and centers.…”
Section: Specific Demands Between Playing Positionsmentioning
confidence: 99%
“…In addition, playing positions present different physical demands [19,20] and technicaltactical actions [21] due to their specific roles in the game. Different adaptations to altitude have been identified across playing positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramos et al found that agility positively in uenced the match performance among U14 basketball players (Ramos et al, 2020). Another Spanish study found that the result of multi-jump tests, the anaerobic capacity, and the agility test had the greatest in uence on the competition (Ibáñez et al, 2023). Against these, Fort-Vanmeerhaeghe et al (Fort-Vanmeerhaeghe et al, 2016) concluded that only the assists and steals per game correlated with any physical eld tests.…”
Section: Introductionmentioning
confidence: 99%
“…The personalization of load should be based on knowledge of the demands imposed by competition [11][12][13]. Reina et al [14] stated that the personalization of external and internal load thresholds allows for tailoring training to the specific characteristics of each player, optimizing physiological adaptation, and enhancing individual performance by adjusting training volume and intensity according to their specific needs, thereby improving physical performance [15,16] and technical-tactical skills [17,18].…”
Section: Introductionmentioning
confidence: 99%